Contribution of dynamic running parameters on gaining maximum running speed of boys in 50 m dash run - Cociv, N.; Smajlovic, N.; Likic, S.; Manic, G.; Kapo, S. (1st International Sport, Science, Education and Development Conference 2015, 2015)
Sprint is characterized as movement of highest running velocity and it is highly genetically conditioned. Early detection of genetic resources can help create a superior sprinter. Maximum running velocity is expressed through the structure of kinematic and dynamic parameters. Prediction of maximum gained speed (KVmax) using dynamic running parameters measured on 50m dash run was conducted on a sample of boys (n = 81, age: 10-12 yrs.). Measurement of dynamic parameters was performed using a software system named BRZ with photo-cells technology. Dynamic running parameters results are presented as mean ± SD in sets of variables: achieved velocity (V), time results at measuring points (T) and time results on split running intervals (TI). Sets of variables V (ß = 14.201, p = 0.000, Adjusted R2 = 0.939), T (ß = 14.009, p = 0.000, Adjusted R2 = 0.925) and TI (ß = 14.063, p = 0.000, Adjusted R2 = 0.929) showed highest significant statistical predictive value. The highest partial contribution (p < 0.05) for prediction of KVmax from the V set are the measured speeds at 15, 20, 25 and 30m, from the T set time results achieved on the 15 and 30m point measurement and in the TI set running time results between 15-20m, 20- 25m and 25-30m. By measuring the basic dynamic parameters of running, it is possible to accurately determine the level of maximal running speed. Boys before puberty, on tested sample, reach maximal running velocities between 15 and 30m. According to the results of research as a part of conclusion, a modified 30m running test was presented suitable when selecting talented boys in the sprint running events.